Zero K : a novel - DeLillo, Don (Scribner, 2016)
The richest, wisest, funniest, and most moving novel in years from Don Delillo, one of the great American novelists of our time-- an ode to language, the heart of our humanity; a meditation on death and an embrace of life. Jeffrey Lockhart's father, Ross, is a George Soros-like billionaire now in his sixties, with a younger wife, Artis, whose health is failing. Ross is the primary investor in a deeply remote and secret compound where death is controlled and bodies are preserved until a future moment when medicine and technology can reawaken them. Jeffrey joins Ross and Artis at the compound to say an uncertain farewell to her as she surrenders her body. Ross Lockhart is not driven by the hope for immortality, for power and wealth beyond the grave. He is driven by love for his wife, for Artis, without whom he feels life is not worth living. It is that which compels him to submit to death long before his time. Jeffrey heartily disapproves. He is committed to living, to the mingled astonishments of our time, here, on earth. Thus begins an emotionally resonant novel that weighs the darkness of the world-- terrorism, floods, fires, famine, death-- against the beauty of everyday life; love, awe, the intimate touch of earth and sun. Brilliantly observed and infused with humor, Don Delillo's Zero K is an acute observation about the fragility and meaning of life, about embracing our family, this world, our language, and our humanity.